Empirical Analysis of the Impact of Inflation Targeting on the Risk Premium - Borivoje D. Krušković; Tina Maričić (Journal of Central Banking Theory and Practice, 2014)
The basis for the conduct of monetary policy is monetary policy strategy. Monetary strategy is necessary for monetary policy makers to analyse all relevant information in order to undertake effective policy actions. Inflation targeting has enabled countries to achieve low inflation in the very short term. Due to this, the financial markets have adjusted their long-term inflation expectations and incorporated them into the interest rate. Risk premiums that compensate for the uncertainty of inflation have fallen. The aim of this paper is to examine how the adoption of inflation targeting affects the movement of the risk premium. The hypothesis we want to test is that the adoption of inflation targeting affects the reduction of the country risk premium by affecting the formation of a more stable macroeconomic environment through a more stable and predictable inflation rate in the medium and long term. The method used for evaluating the regression coefficients is the dynamic panel generalized method of moments (GMM). This method involves the use of conditional moments in endogenous and exogenous variables with a lag as instruments for the assessment of differential equations, while the difference lagged endogenous variables are used as instruments in the levels equation.
Keywords: E31; E52; E58; 330; inflation targeting; inflation risk premiums; asset prices; monetary strategy